2011
DOI: 10.1074/jbc.m111.290825
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Src and Focal Adhesion Kinase Promote Endocrine Specification

Abstract: Background: Signaling mechanisms regulating the endocrine specification of stem cell derivatives. Results: Inhibiting Src family kinase (SFK) and focal adhesion kinase (FAK) activity promotes endocrine commitment. Conclusion: Select inhibitors of SFK/FAK signaling increase the derivation of ␤-cells. Significance: Enhanced derivation of insulin-producing ␤-cells for the cell-based therapy of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…These results are similar to those demonstrating that the selective tyrosine kinase inhibitor imatinib promotes INS release from β cells32. In addition, the blockade of tyrosine kinase signalling, such as Src family kinases and FAK, can promote β cell differentiation33. Thus, there is growing evidence that tyrosine kinase signalling has a role in the differentiation of β cells as well as in maintaining the function of mature β cells.…”
Section: Discussionsupporting
confidence: 85%
“…These results are similar to those demonstrating that the selective tyrosine kinase inhibitor imatinib promotes INS release from β cells32. In addition, the blockade of tyrosine kinase signalling, such as Src family kinases and FAK, can promote β cell differentiation33. Thus, there is growing evidence that tyrosine kinase signalling has a role in the differentiation of β cells as well as in maintaining the function of mature β cells.…”
Section: Discussionsupporting
confidence: 85%
“…Half of the spheres were transferred to one plate and kept in a growth medium (control), and the other half were kept in a differentiation medium, which contained DMEM high glucose, B27 supplement and PP2, a Src family kinase inhibitor, since we recently showed that Src family kinase inhibition is involved in endocrine specification. 27 After 4 days, the spheres were harvested and analyzed for pancreatic markers of progenitor and hormone-expressing cells. We found robust expression of Pdx1 , Nkx6.1 , insulin, glucagon, and somatostatin in SSEA4 + in comparison to the controls and to SSEA4 − cell-derived spheres (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…mRNA purification, cDNA synthesis, and real-time quantitative polymerase chain reaction (RT-qPCR) analysis of differentiated tissue were performed as previously described. 27 Briefly, 20 μL PCR reactions were run using 3 μL of cDNA, combined with the TaqMan Universal PCR Master Mix (4324018; Applied Biosystems) and unlabeled PCR primers and a TaqMan FAM ™ dye-labeled probe listed in Supplementary Table S1. RT-qPCR was performed using an Applied Biosystems StepOnePlus real time PCR machine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The self-organization of endocrine progenitors into islet structure appears to be mediated by G-protein coupled receptors, non-canonical Wnt, and receptor tyrosine kinase (RTK) signaling [45]. While the importance of delamination and migration to in vitro derivation of endocrine cells from hPSC is not known, endocrine differentiation is promoted in the presence of focal adhesion kinase inhibitor, suggesting that modulation of EMT-related pathways may control endocrine specification in hPSC culture [46]. …”
Section: Cell Migration Creates Isletsmentioning
confidence: 99%